Tracing Srivijayan Buddhist Heritage in Riau: Linguistic, Ritual and Material Evidence of Cultural Continuity - Suroyo; Ervantia Restulita Liber SIgai; Novena Ade Fredyarini Soedjiwo; Bima Maulana Putra; Saida Kheira Benammar (Center for Research and Development of Religious Literature and Heritage, 2025)
Malay cultural identity is often interpreted primarily through Islamic frameworks, which has led to the marginalization of earlier cultural layers that shaped its formation. This study addresses a significant gap in Malay historiography, namely the limited examination of how Srivijayan Buddhist cultural structures continue to influence contemporary Malay identity in the Riau mainland. The research employs a qualitative historical‑interpretive design that integrates ethnographic observation, Old Malay epigraphic materials, Chinese Buddhist records, and archaeological data from Muara Takus and related sites. Textual comparison, historical linguistics and material culture analysis were used to identify patterns of continuity between Srivijayan Buddhist traditions and present-day cultural practices. The findings reveal three major continuities. First, purification rituals such as petang megang retain pre-Islamic Buddhist concepts of spatial and temporal cleansing. Second, communal eating traditions preserve Old Malay social ethics centered on equality and collective cohesion. Third, linguistic survivals in Riau Malay, including Old Malay lexicon and phonological features, demonstrate long-term structural continuity with Srivijayan-era language use. These continuities show that Islamic transformation in Riau did not replace earlier cultural systems but adapted and integrated them.